Activist Essayism - Paul Woolridge (Opticon1826, 2007)
Any study of the essay is bound to run into the problem of classification, even more modest inquiries like this one which restrict the genre’s range to twentieth-century Anglo-American literary life. To speak of ‘the essay’, in fact, is already to invoke it as a distinct form of writing, a genre to itself, a rubric under which each individual instance engenders some larger, definitive set of shared criteria. We speak in similar presupposing terms about the novel, the lyric poem, the short story and the epic (among the many others) as literary objects, written forms defined and characterised by larger generic categories. The essay, to be sure, has many such distinguishable features which mark it off as at least a minor literary genre recognisable apart from the rest. Spontaneous, brief, sceptical, ambulatory, tentative, exploratory, subjective, experiential, conversational, fragmentary, elastic, unmethodical and free are some of the more common epithets imputed to its form. As Graham Good observes, ‘many good insights into the potentials of the essay form can be gained from the titles of collections’, especially when drawn from critical and self-reflexive characterisations focused on the essay form itself.1
Keywords: essay-writing; activism